Implementasi Peraturan Daerah Kabupaten Solok Nomor 7 Tahun 2018 Tentang Pengelolaan Sampah Di Nagari Sungai Nanam Kecamatan Lembah Gumanti Oleh Walinagari - Syahputri Julia Anggraini; Fiolani Grescia Falendra; Putri Ryvinasya Lidra; Natasya Fortuna; Warida Jasmiza; Kiki Fadhila Putra; Elwidarifa Marwenny (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Sungai Nanam Village has faced serious challenges in managing waste piled up on the roadside since 2021 due to the lack of a final disposal site that pollutes the environment with rotting waste, causing air pollution and damaging the beauty and aesthetics of the environment. Although the community has made efforts to reduce waste disposal into the river through community service and collaboration with the Environmental Agency, the waste problem remains a significant issue despite the existence of Solok Regency Regulation Number 7 of 2018 concerning Waste Management, thus raising the following questions: 1) How is the implementation of Solok Regency Regulation Number 7 of 2018 concerning Waste Management in Sungai Nanam Village? 2) What obstacles does Sungai Nanam Village face in waste management? 3) What is the urgency of creating a Village Regulation related to waste management? To answer these questions, an empirical juridical research method was used through interviews. The research approach used a statute approach and a case approach, resulting in the following conclusions: 1) The implementation of Solok Regency Regulation No. 7 of 2018 in Sungai Nanam Village has not been implemented properly because the Village Regulation is still in the process of being drafted and has not been ratified; 2) Obstacles faced in waste management are the lack of facilities (Final Disposal Sites and Dump Trucks), low public awareness, inconsistent enforcement of sanctions and limited Human Resources and budgets also weaken the sustainable waste management system; 3) The preparation of Village Regulations is very urgent to be carried out to support the implementation of Regional Regulations at the local level as well as a technical legal basis that is in accordance with village conditions, strengthens guidance, supervision, and sanctions, and encourages community participation in waste management effectively and sustainably.